2013
DOI: 10.1111/nyas.12055
|View full text |Cite
|
Sign up to set email alerts
|

Force‐sensitive afferents recruited during stance encode sensory depression in the contralateral swinging limb during locomotion

Abstract: Afferent feedback alters muscle activity during locomotion and must be tightly controlled. As primary afferent depolarization-induced presynaptic inhibition (PAD-PSI) regulates afferent signaling, we investigated hind limb PAD-PSI during locomotion in an in vitro rat spinal cord-hind limb preparation. We compared the relation of PAD-PSI, measured as dorsal root potentials (DRPs), to observed ipsilateral and contralateral limb endpoint forces. Afferents activated during stance-phase force strongly and proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…Thus, there are no data on the effects of oxytocin in integrating afferent inputs into the CPG. The role of primary afferents in modulating the locomotor pattern is linked to the existence of sensory feedbacks evoked during gait to physiologically control, at a pre-synaptic level, incoming inputs to the spinal cord [34] , and to convey facilitatory signals to the CPG via multisegmental sacrocaudal afferents [35] , even with nociceptive content [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are no data on the effects of oxytocin in integrating afferent inputs into the CPG. The role of primary afferents in modulating the locomotor pattern is linked to the existence of sensory feedbacks evoked during gait to physiologically control, at a pre-synaptic level, incoming inputs to the spinal cord [34] , and to convey facilitatory signals to the CPG via multisegmental sacrocaudal afferents [35] , even with nociceptive content [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, dorsal cells phasically depolarize during each ipsilateral VR burst . Earlier reports have shown a role of (electrically induced) contralateral afferent activity in the generation of DRPs in the opposite limb during hindpaw swing . Similarly, literature has shown that, during FL, the sensory inflow to the swing limb can be increased by presynaptic inhibition based on forces generated by the (contralateral) stance limb .…”
Section: Discussionmentioning
confidence: 90%
“…Hochman focused on presynaptic inhibition (PSI) recorded as a primary afferent depolarization (PAD) in the neonatal rat spinal cord with hindlimb attached. In this preparation that expresses actual locomotor movements of its hindlimbs, it is possible to monitor (1) the PAD with suction electrodes attached to dorsal roots and (2) motor neuron action potentials with suction electrodes attached to ventral roots.…”
Section: Neuronal Circuits In the Spinal Cord And Brainstemmentioning
confidence: 99%
“…The goal of this report is to highlight four spinal cord and brainstem themes discussed by speakers at the 2012 conference and authors of the present volume: neurogenetics, circuits, plasticity, and translational impacts. This report will discuss the contents of the summaries of the oral presentations of the conference and published data presented by speakers during the oral sessions . Space limitations prevent detailed descriptions of every important result, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation